EGFR ligands synergistically increase IL‐17A‐induced expression of psoriasis signature genes in human keratinocytes via IκBζ and Bcl3. Issue 6 (22nd April 2022) - Dai, Xiuju; Murakami, Masamoto; Shiraishi, Ken; Muto, Jun; Tohyama, Mikiko; Mori, Hideki; Utsunomiya, Ryo; Sayama, Koji
Abstract: Various epidermal growth factor receptor (EGFR) ligands are highly expressed in the epidermis of psoriasis lesions, and abnormal EGFR activation appears to be involved in the pathogenesis of psoriasis. However, how EGFR signaling contributes to the development of psoriasis is unclear. Interleukin (IL)‐17A, a critical effector of the IL‐23/IL‐17A pathway, increases the expression of psoriasis signature genes in keratinocytes and plays an essential role in the pathogenesis of psoriasis by inducing IκBζ, a critical transcriptional regulator in psoriasis. In this study, we stimulated primary human keratinocytes with IL‐17A and various EGFR ligands to investigate whether EGFR ligands regulate the expression of psoriasis signature genes. In cultured normal human keratinocytes and a living skin equivalent, EGFR ligands did not induce psoriasis‐related gene expression, but significantly enhanced the IL‐17A‐mediated induction of various psoriasis signature genes, including antimicrobial peptides, cytokines, and chemokines. This was dependent on an EGFR activation‐mediated synergistic increase in IL‐17A‐induced IκBζ expression and was partially mediated by the EGFR‐dependent upregulation of Bcl3. Therefore, EGFR ligands can act as synergistic agents of IL‐17A signaling by stimulating the epidermal production of psoriasis signature genes in psoriasis lesions. This study reveals a potential mechanism by which EGFR signaling contributes to the pathogenesis of psoriasis. Abstract : EGFR ligands contribute to the pathogenesis of psoriasis by potentiating IL‐17A signaling and synergistically increasing the expression of IL‐17A‐induced psoriasis signatures genes in epidermal keratinocytes, which both IκBζ and Bcl3 mediate.